2022
DOI: 10.1021/acs.molpharmaceut.1c00761
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Activated Multifunctional Prodrug Combining Site-Specific Chemotherapy with Light-Triggered Photodynamic Therapy

Abstract: Combination treatments are more effective than conventional monotherapy in combating cancer. Herein, a multifunctional prodrug BDP-L-CPT was rationally engineered and prepared by the conjugation of a boron dipyrromethene (BDP)-based photosensitizer (PS) to the active site of the chemotherapeutic drug camptothecin (CPT) via a phenyl benzoate group. After modification, the cytotoxicity of CPT was locked. Moreover, the fluorescence emission at 430 nm from the CPT component in the prodrug was substantially inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…When the prodrug interacts with carboxylesterases, the ester bond can be broken, releasing the PS and CPT anticancer drugs, and then the PS can play its therapeutic role under UV radiation. In cell assay and in vivo experiments, prodrug 42 against human hepatocellular carcinoma (HepG2) and human cervical carcinoma cells (HeLa) were lower than those of the controls, 83 BDP-COOH, and CPT (Fig. 25).…”
Section: Enzyme-activated Systemmentioning
confidence: 98%
See 1 more Smart Citation
“…When the prodrug interacts with carboxylesterases, the ester bond can be broken, releasing the PS and CPT anticancer drugs, and then the PS can play its therapeutic role under UV radiation. In cell assay and in vivo experiments, prodrug 42 against human hepatocellular carcinoma (HepG2) and human cervical carcinoma cells (HeLa) were lower than those of the controls, 83 BDP-COOH, and CPT (Fig. 25).…”
Section: Enzyme-activated Systemmentioning
confidence: 98%
“…In addition, Liu et al 83 reported enzyme-activated multifunctional prodrug 42 . This prodrug can provide three functions: imaging of drug release, photodynamic therapy, and chemotherapy.…”
Section: Enzyme-activated Systemmentioning
confidence: 99%
“…Among the TI category and in the field of anticancer nanomedicines, the natural drug camptothecin (CTP) (see Section 4.4 ) is particularly appealing to be modified and synthetized in the form of prodrugs, often in combination with PSs [ 149 , 150 , 151 ], and to be further utilized for the formation of carrier-free NPs [ 152 , 153 ]. As an example, Chu and co-workers reported on the synthesis of a novel ROS-responsive nanosystem (MPEG-(TK-CPT)-PPa) derived from the self-assembly of a prodrug of CPT and pyropheophorbide (PPa) both conjugated to a PEG methyl ether (MPEG) via a TK and lipid linkage, respectively [ 109 ].…”
Section: Drug Delivery Systems For Pss and Chemotherapeutics: An Over...mentioning
confidence: 99%
“…The CE activity was then effectively evaluated in orthotopic HepG2 tumor‐bearing mice under different conditions and 3D imaging in vivo. To afford the cancer‐killing ability, Zhang and colleagues developed a CE‐triggered multifunctional prodrug BDP−L−CPT (Figure 13) by the conjugation of a boron dipyrromethene (BDP)‐based PS to the active site of the chemotherapeutic drug camptothecin (CPT) [79] . The activity of CPT was effectively shielded in the prodrug by chemical modification.…”
Section: Enzyme‐responsive Probes Based On Functional Groupsmentioning
confidence: 99%